Efficacy of Low-Frequency Repetitive Transcranial Magnetic Stimulation in Ischemic Stroke: A Double-Blind Randomized Controlled Trial - Sharma, H. (Arch Rehabil Res Clin Transl, 2020)
OBJECTIVE: To investigate the role of low-frequency repetitive transcranial magnetic stimulation (rTMS) along with conventional physiotherapy in the functional recovery of patients with subacute ischemic stroke. DESIGN: Double-blind, parallel group, randomized controlled trial. SETTING: The outpatient department of a tertiary hospital participants: first ever ischemic stroke patients (N=96) in the previous 15 days were recruited and were randomized after a run-in period of 75±7 days into real rTMS (n=47) and sham rTMS (n=49) groups. INTERVENTION: Conventional physical therapy was given to both the groups for 90±7 days postrecruitment. Total 10 sessions of low-frequency rTMS on contralesional premotor cortex was administered to real rTMS group (n=47) over a period of 2 weeks followed by physiotherapy regime for 45-50 minutes. MAIN OUTCOME MEASURES: The primary efficacy outcomes were change in modified Barthel Index (mBI) score (pre- to postscore) and proportion of participants with mBI score more than 90, measured at 90±7 days postrecruitment. The secondary outcomes were change in Fugl-Meyer Assessment–upper extremity, Fugl-Meyer Assessment–lower extremity, Hamilton Depression Scale, modified Rankin Scale, and National Institute of Health and Stroke Scale (pre- to post-rTMS) scores at 90±7 days post recruitment. RESULTS: Modified intention to treat analysis showed a significant increase in the mBI score from pre- to post-rTMS in real rTMS group (4.96±4.06) versus sham rTMS group (2.65±3.25). There was no significant difference in proportion of patients with mBI>90 (55% vs 59%; P=.86) at 3 months between the groups. CONCLUSION: In patients with subacute ischemic stroke, 1-Hz low-frequency rTMS on contralesional premotor cortex along with conventional physical therapy resulted in significant change in mBI score.